Potential of Dimethyl Sulfoxide Modified Kaolin and Cetyl Trimethylammonium Bromide as Amoxycillin Adsorben - Gatut Ari Wardani; Ratih Damayanti; Mochamad Fathurohman; Taufik Hidayat; Estin Nofiyanti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
The large use of amoxicillin allows this antibiotic to enter the environment in large quantities and cause pollution. The adsorption technique can be used as a method to remove amoxicillin contaminants in wastewater by utilizing kaolin as an adsorbent. This study aims to determine the characteristics of kaolin as an adsorbent and determine the ability of kaolin to adsorb amoxicillin. Kaolin was activated with hydrochloric acid and modified using Dimethyl sulfoxide (DMSO) and cetyl trimethylammonium bromide (CTAB). The results showed that the characteristics of DMSO and CTAB-modified kaolin showed a new peak which was an O-H bending vibration in functional group analysis using FTIR. X-ray diffraction results show that the distance between planes in the kaolin structure is larger. Meanwhile, the results of the SEM analysis showed that the surface morphology of kaolin had a higher level of crystallinity than before which proved an increase in the adsorption capacity of kaolin. The adsorption kinetics follows the Santosa kinetic equation model with an adsorption rate of 0.004 min-1 and an equilibrium constant value of 0.007 L.mol-1. The adsorption isotherm test follows the Freundlich isotherm equation model with an adsorption constant value of 561.694 L.mg-1 and an empirical constant value of 0.270.Â Keywords: Antibiotics, Adsorption, Batch, Isotherms, Kinetics